Load-distributing-band cardiopulmonary resuscitation for out-of-hospital cardiac arrest increases regional cerebral oxygenation: a single-center prospective pilot study - Ogawa, Yoshihito; Shiozaki, Tadahiko; Hirose, Tomoya; Ohnishi, Mitsuo; Nakamori, Yasushi; Ogura, Hiroshi; Shimazu, Takeshi (Scandinavian journal of trauma, resuscitation and emergency medicine, 2015)
Despite advances in therapeutic strategies and improved guidelines, morbidity and mortality rates for out-of-hospital cardiac arrest (OHCA) remain high. Especially, neurological prognosis is one of the most important problems even though brain protection therapy for patients with OHCA has improved greatly in recent years due to the development of emergency post-cardiac arrest interventions such as mild therapeutic hypothermia, early percutaneous coronary intervention, and extracorporeal cardiopulmonary resuscitation (CPR). Recently, cerebral regional oxygen saturation (rSO2) has received attention as a method for evaluation of cerebral oxygenation. We have reported that conventional chest compression did not improve the rSO2 of cardiac arrest patients if they did not achieve return of spontaneous circulation. It is, however, unclear whether a mechanical CPR device is helpful in improving rSO2. The purpose of this study was to evaluate the effects of load-distributing-band CPR (LDB-CPR) on rSO2. In this prospective study, LDB-CPR was begun for OHCA with the AutoPulse(TM) device on patient arrival at hospital. During mechanical CPR, rSO2 values were recorded continuously from the forehead of the patients. CPR for patients with OHCA was performed according to the Japan Resuscitation Council Guidelines 2010 except for using the AutoPulse(TM) instead of manual chest compression. From December 2012 to December 2013, 34 patients (mean age, 75.6 ± 12.8 years) with OHCA were included in this study. Duration of time from recognition of cardiac collapse to arrival to hospital was 31.0 ± 11.4 min. Compared with the rSO2 value of 38.9 ± 0.7 % prior to starting LDB-CPR, rSO2 values at 4, 8 and 12 minutes increased significantly after initiation of LDB-CPR (44.0 ± 0.9 %, 45.2 ± 0.8 %, and 45.5 ± 0.8 %, respectively, p < 0.05). LDB-CPR significantly increased the rSO2 of cardiac arrest patients during resuscitation.